The Role of The Iraqi Private Sector in Taking Advantage of International Economic Integration Opportunities - Baydaa Jawad Kazem (International Journal on Economics, Finance and Sustainable Development, 2026)
The Iraqi private sector has tremendous potential to capitalize on international economic integration opportunities by enhancing its competitiveness, expanding its exports, attracting foreign investment, and contributing to infrastructure development and knowledge transfer. However, the Iraqi private sector faces significant challenges that require concerted efforts between the public and private sectors to overcome. These challenges include the unstable security and political situation, bureaucratic corruption, weak infrastructure, and difficulty accessing financing. To overcome these obstacles and maximize the private sector's benefits from economic integration , the study recommends that the Iraqi government improve the business environment, facilitate procedures, provide investment incentives, develop infrastructure, support small and medium-sized enterprises, and combat corruption. The study also emphasizes the importance of the private sector itself developing its capabilities, investing in innovation and quality, and building strategic partnerships with international companies. Activating the role of the private sector and enabling it to exploit international economic integration opportunities represents a crucial step toward achieving sustainable economic development and a prosperous future for Iraq.